2021
DOI: 10.1097/aud.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Diagnostic Approach to Patients Suspected of Superior Semicircular Canal Dehiscence

Abstract: Objectives: Current methods of diagnosing superior semicircular canal dehiscence syndrome (SCDS) include a clinical exam, audiometric testing, temporal bone computer tomography (CT) imaging, and vestibular evoked myogenic potential (VEMP) testing. The main objective of this study was to develop an improved diagnostic approach to SCDS optimized for accuracy, efficiency, and safety that utilizes clinical presentation, audiometric testing, CT imaging, high-frequency cervical VEMP (cVEMP) testing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Once again, the evidence of this study shows that 4000Hz is an excellent test for identifying SCD. We agree with the conclusion of Noij et al: "VEMP tests using high frequency stimuli are the most accurate single diagnostic test for SCD " [17,18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Once again, the evidence of this study shows that 4000Hz is an excellent test for identifying SCD. We agree with the conclusion of Noij et al: "VEMP tests using high frequency stimuli are the most accurate single diagnostic test for SCD " [17,18].…”
Section: Discussionsupporting
confidence: 92%
“…Thus a single test, averaging the response to just 50 stimuli at 4000Hz, is a very valuable initial screening test for patients with a suspected SCD [15,16]. Recent developments have been refined to optimize both sensitivity and specificity of high frequency cVEMP and oVEMP for detecting SCD and it has been argued that "VEMP tests using high frequency stimuli are the most accurate single diagnostic test for SCD " [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the evidence demonstrates that, once again, 4000 Hz is an excellent test for identifying SCD. We fully agree with the statement by Noij et al that “VEMP tests using high frequency stimuli are the most accurate single diagnostic test for SCD“ [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, in this study, as in our previous study [ 15 ], every single CT-verified SCD patient showed an oVEMP n10 to the 4000 Hz stimuli with short rise times (15 patients in this study, 26 patients in our previous study, for a total of 41 patients with 100% detection). This is convincing evidence that 4000 Hz with a short rise time is an excellent screening test for SCD [ 18 ]. As we have shown, the result is in close accordance with the evidence from the physiology of the effect of SCD on canal afferent neuron responses.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation